Clinical Reasoning Assessment Methods in Prelicensure Undergraduate Nursing Education: A Scoping Review Protocol - Li Sze, Chai; Azlina, Yusuf; Muhamad Saiful Bahri, Yusoff (Malaysian Association of Education in Medicine and Health Sciences and Penerbit Universiti Sains Malaysia., 2024)
Assessing the clinical reasoning process is challenging due to its limited direct observability, requiring diverse methods. A comprehensive review of diverse assessment methods, revealing intricate details of clinical reasoning, would assist in selecting methods tailored to the aim of the clinical reasoning assessment in prelicensure undergraduate nursing education. This scoping review protocol outlines a plan to explore the clinical reasoning assessment methods used in prelicensure undergraduate nursing education. The characteristics of identified clinical reasoning assessment methods will be examined by analysing definition or conceptualisation of clinical reasoning being used in the assessment, the theoretical framework underpinning the conceptualisation of clinical reasoning and its assessment, stimulus format, response format, the scoring activity employed, rater information, validity evidence and reliability measures. The focus will be on primary quantitative and qualitative research, excluding non-research publications. Following the Joanna Briggs Institute (JBI) methodology, a three-step search strategy will be employed. The review will search Scopus, EBSCO Host (CINAHL and MEDLINE), PubMed, Science Direct, Web of Science and Epistemonikos. Unpublished studies will be sought in ProQuest Dissertation and Theses. All studies available up to the date of the literature search and published in English will be considered. Evidence source details and essential components in clinical reasoning assessment methods will be extracted. Key findings obtained during the data extraction process will be reported, organised into tabular presentations, focusing on the characteristics of clinical reasoning assessment methods in prelicensure undergraduate nursing education.